Position Paper by Canadian Dental Sleep Medicine Professionals Regarding the Role of Different Health Care Professionals in Managing Obstructive Sleep Apnea and Snoring with Oral Appliances. Issue 5 (2012) - Gauthier, Luc; Almeida, Fernanda; Arcache, Patrick; Ashton-McGregor, Catherine; Côté, David; Driver, Helen; Ferguson, Kathleen; Lavigne, Gilles; Martin, Philippe; Masse, Jean-François; Morisson, Florence; Pancer, Jeffrey; et al.
Abstract : The present Canadian position paper contains recommendations for the management by dentists of sleep-disordered breathing in adults with the use of oral appliances (OAs) as a treatment option for snoring and obstructive sleep apnea (OSA). The recommendations are based on literature reviews and expert panel consensus. OAs offer an effective, first-line treatment option for patients with mild to moderate OSA who prefer an OA to continuous positive airway pressure (CPAP) therapy, or for severe OSA patients who cannot tolerate CPAP, are inappropriate candidates for CPAP or who have failed CPAP treatment attempts. The purpose of the present position paper is to guide interdisciplinary teamwork (sleep physicians and sleep dentists) and to clarify the role of each professional in the management of OA therapy. The diagnosis of OSA should always be made by a physician, and OAs should be fitted by a qualified dentist who is trained and experienced in dental sleep medicine. Follow-up assessment by the referring physician and polysomnography or sleep studies are required to verify treatment efficacy. The present article emphasizes the need for a team approach to OA therapy and provides treatment guidelines for dentists trained in dental sleep medicine. Many of the dentists and sleep physicians who contributed to the preparation of the present article are members of the Canadian Sleep Society and the authors reached a consensus based on the current literature.